CHALLENGES IN CORRUPTION ERADICATION - Agus Raharjo (Faculty of Law, Universitas Jenderal Soedirman, 2015)
The government of Joko Widodo - Jusuf Kalla at the beginning of this year is faced a fairly complicated issue related to the eradication of corruption. Corruption eradication’s program which is launched by the goverment, really tested well with many variety of incident that shocked the law enforcement against corruption. A brave way of Corruption Eradication Commission (KPK) establish Police Commissioner General Budi Gunawan as the suspects, get a praise from the public, but he gets a resistance from the police institution. This reaction is reasonable because the Commissioner General Budi Gunawan is a police officials who already have a KPK radar connection related to the fat bank accounts.......